Business Cycles in Emerging Markets : The Role of Durable Goods and Financial Frictions. (IMF Working Papers; Working Paper ;, 2011)
This paper examines how durable goods and financial frictions shape the business cycle of a small open economy subject to shocks to trend and transitory shocks. In the data, nondurable consumption is not as volatile as income for both developed and emerging market economies. The simulation of the model implies that shocks to trend play a less important role than previously documented. Financial frictions improve the ability of the model to match some key business cycle properties of emerging economies. A countercyclical borrowing premium interacts with the nature of durable goods delivering highly volatile consumption and very countercyclical net exports.